Patient preferences for autonomy in decision making in asthma management. Issue 2 (1st February 2001) - Adams, R J; Smith, B J; Ruffin, R E
Abstract : BACKGROUND: Lower patient preferences for autonomy in management decision making during asthma exacerbations have been associated with an increased risk for future hospital admissions. We sought to examine patient preferences for asthma self-management autonomy, and the clinical and psychosocial factors associated with autonomy preferences. METHODS: A cross sectional observational study was performed with data collected between June 1995 and December 1997 of 212 adult patients with moderate to severe asthma managed, at least in part, at two teaching hospitals. Subjects completed a survey of autonomy preferences, quality of life, clinical morbidity and health service use, asthma knowledge, self-efficacy, coping styles, and psychosocial measures. RESULTS: Patients preferred clinicians to assume the major role in most decision making about their management. However, patients wished to remain in control in choosing when to seek care and wanted to share decisions regarding initiating changes in medications during a moderate exacerbation. Multiple regression analysis showed that concerns about adverse effects of medications, education level, an active coping style, perceptions of the propensity of physicians to involve them in treatment decision making, and concerns about costs causing delays in seeking medical care were associated with preferences for autonomy in decision making. Autonomy preferences were not related to measures of concurrent clinical asthma control or health related quality of life. CONCLUSIONS: In a group of patients with moderate to severe asthma, a high proportion of whom were from socioeconomically disadvantaged backgrounds, education level, perceived physician behaviour, cost barriers to care, and psychosocial factors (but not clinical asthma control or management) were related to patient preferences for autonomy in management decision making during asthma exacerbations. This has implications for asthma action plans and design of self-management programmes.